Pemanfaatan Blended Learning Edmodo Grup dalam Pempelajaran Mata Kuliah Membaca - Asnawi, Asnawi (GERAM: Gerakan Aktif Menulis, 2017)
Reading is an activity to understand reading material effectively. Reading became the biggest problem for students these days. This is due to a lack of reading motivation and a lack of awareness of reading needs. Students more often open handpone applications rather than books. Such conditions affect the learning of reading courses for students in the first level. To create a more enjoyable reading activity, it needs to be utilized and combined with the blanded learning by using edmodo group application. Edmodo group is a social media as a means of liaison between students, teachers, and parents. Edmodo is also used as a learning electronic e-learning platform. This research is formulated by how is the utilization of blanded learning edmodo group in reading activity? The purpose of this research is to know the utilization of edmodo group in reading. This research is a kind of qualitative research with descriptive method of data presentation. Data collection techniques in this study using a questionnaire which analyzing simple description percentage. The results of this study are providing a fun learning method, making the relationship of lecturers with students to be closer, facilitate communication between lecturers and students, learning can be done anytime, as a suggestion to share knowledge and knowledge with new people, and as a media completion of exercises, and quiz.